Use of gaseous ozone to reduce aflatoxin B1 and microorganisms in poultry feed. (July 2016) - Torlak, Emrah; Akata, Ilgaz; Erci, Fatih; Uncu, Ali Tevfik
Abstract: This study was undertaken to evaluate the efficacy of gaseous ozone for the degradation of aflatoxin B1 (AFB1 ) and inactivation of indigenous microflora in poultry feed. Feed samples were treated with continuous stream of two different constant concentrations (2.8 and 5.3 mg/L) of ozone at room temperature up to 240 min. The initial AFB1 level in artificially contaminated feed samples, determined as 32.8 μg/kg, decreased by 74.3 and 86.4% after 240 min of exposure at 2.8 and 5.3 mg/L, respectively. At the both ozone concentrations, 240 min exposure was reduced the aerobic plate and yeast and mold counts below the detection limit (<10 CFU/g) with a reduction more than 3.2 and 2.7 log, respectively. The thiobarbituric acid reactive substances (TBARS) assay indicated that no significant ( P  ≥ 0.05) increase occurred in the level of lipid oxidation in feed samples during 120 min ozonation at 2.8 mg/L. At the end of the 240 min of exposure at 2.8 and 5.3 mg/L, initial TBARS concentration, determined as 2.4 mg/kg, reached to 4.4 and 5.3 mg/kg with a significant ( P  < 0.05) increases, respectively. The results presented in this study suggested that significant ( P  < 0.05) reductions in the AFB1 level and microbial population can be achieved in poultry feed by ozonation with an acceptable changes in lipid oxidation. Highlights: Poultry feed was ozonated at the concentrations of 2.8 and 5.3 mg/L for up to 240 min. Ozonation for 240 min yielded up to 86.4% reduction in the aflatoxin B1 level. Ozonation for 120 min resulted in microbial reductions ranging from 2.3 to 3.2 log CFU/g. Ozonation at 2.8 mg/L up to 120 min did not caused significant changes in the lipid oxidation.